Anatomy & physiology - Seeley, Rod R; Stephens, Trent D.; Tate, Philip (London : Mosby Year Book, 1992)
Organization of the human body.--Support and movement.--Integration and control systems.--Regulation and maintenance.--Reproduction and development.
Incluye Apéndices.-- Glosario
Keywords: Anatomía; Fisiología humana